Comparison of Genial Tubercule Anatomy Based on Age and Gender - Beyza Karadede Ünal; İsmail Hamit Hancı; Emre Aytuğar; Ferhan Elmalı; Berşan Karadede; Özkan Büyük; Nuri Ünal; Mehmet İrfan Karadede (Galenos Yayinevi, 2021)
Objective: In our study, it was aimed to determine whether there were differences in genial tubercle dimensions depending on age and gender.Methods: In this study, 220 cone beam computed tomography (CBCT) images of patients (110 female and 110 male) between the ages of 20-80 years were obtained from the archive of İzmir Katip Çelebi University Faculty of Dentistry. All patients were divided into decade groups according to their age, and each decade group was divided into two subgroups according to gender. The genial tubercle was defined radiologically using axial, coronal and sagittal sections as well as 3D reconstruction image with NNT software program. Sagittal, vertical and horizontal dimensions of the genial tubercle were measured and statistically analyzed.Results: There was a weak negative correlation between age groups and vertical values (r=-0.142; p=0.036) whereas the correlation coefficients between age groups and sagittal and horizontal values were not statistically significant (r=-0.043; p=0.530 and r=-0.039; p=0.563). There was a strong positive correlation between vertical and sagittal values in men (r=0.705, p<0.001) and women (r=0.714, p<0.001) in the whole group. There was a weak positive correlation between horizontal and sagittal, horizontal and vertical values in men (r=0.362, p<0.001; r=0.231, p<0.001) and women (r=0.304, p<0.001; r=0.257, p=0.007) in the whole group.Conclusion: The vertical and horizontal dimensions of genial tubercle of men were higher than that of women. As the age of the patients increased, a decrease in the vertical values of the genial tubercle was observed.